Students’ attitude and difficulties in practicing speaking through autonomous learning on podcast - Nurunnisa Rachma Buana; Miftachudin (Erudita: Journal of English Language Teaching, 2021)
This research aims to examine the students’ attitude on producing podcasts as a media to practice speaking for autonomous learning and the difficulties faced by students in producing podcast of speaking. This research was descriptive qualitative research and the data is collected using questionnaire and semi-structured interview. As many 28 students of English Education Department of one of public Islamic institution in Central Java in various semesters participated in the questionnaire and 4 students were chosen to be interviewed to validate the information from the questionnaire. The research found that the majority of the students have positive attitude towards producing podcasts activity as their media to practice their speaking. In the affective aspect, students are excited with the process and behaviorally they are encouraged to prepare the material well. In the cognitive aspect, students consider the activity of producing podcast is a great activity for beginner students. They are assisted to autonomously practice speaking without partner which allows them to evaluate their own quality of speaking particularly in pronunciation. Students faced many difficulties such as speaking anxiety, complex preparation, and the inconvenience of doing repeated recording.